2018
DOI: 10.1038/s41467-018-05245-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of DNA target searching and cleavage by CRISPR-Cas12a

Abstract: Cas12a (also called Cpf1) is a representative type V-A CRISPR effector RNA-guided DNA endonuclease, which provides an alternative to type II CRISPR–Cas9 for genome editing. Previous studies have revealed that Cas12a has unique features distinct from Cas9, but the detailed mechanisms of target searching and DNA cleavage by Cas12a are still unclear. Here, we directly observe this entire process by using single-molecule fluorescence assays to study Cas12a from Acidaminococcus sp. (AsCas12a). We determine that AsC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
145
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(171 citation statements)
references
References 61 publications
(82 reference statements)
22
145
0
Order By: Relevance
“…Similarly, RPA amplified products are also the substrates to undertake the same process and continuously trigger CRISPR-Cas12a-based collateral cleavage activity. Previous study 14,17 has demonstrated that this collateral cleavage activity is irrelevant to target strand cleavage in CRISPR-Cas12a system. Therefore, target sequences for the AIOD-CRISPR assay are not limited by the Cas12a's protospacer adjacent motif (PAM) 21 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, RPA amplified products are also the substrates to undertake the same process and continuously trigger CRISPR-Cas12a-based collateral cleavage activity. Previous study 14,17 has demonstrated that this collateral cleavage activity is irrelevant to target strand cleavage in CRISPR-Cas12a system. Therefore, target sequences for the AIOD-CRISPR assay are not limited by the Cas12a's protospacer adjacent motif (PAM) 21 .…”
Section: Introductionmentioning
confidence: 97%
“…11,12 For example, some Cas nucleases (e.g., Cas12a, Cas12b and Cas13a) perform strong collateral cleavage activities in which a crRNA-targetbinding activated Cas can indiscriminately cleave surrounding non-target single-stranded nucleic acids. 13,14,15,16,17 By combining with RPA preamplification, Cas13 and Cas12a have, respectively, been used to develop SHERLOCK (Specific High-sensitivity Enzymatic Reporter UnLOCKing) system 18 and DETECTR (DNA Endonuclease-Targeted CRISPR Trans Reporter) system 14 for highly sensitive nucleic acid detection. Apart from RPA method, some CRISPR-Cas-based nucleic acid sensors utilized the LAMP and PCR approaches, for instance, the CRISPR-Cas12b-assisted HOLMESv2 platform.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally for Cas9, it has been shown that crRNA and tracrRNA can be fused into a ~100 nucleotide (nt) single-guide (sgRNA) and that the 3' end of the non-target strand can be partially degraded after the blunt cut is made to leave a 5' overhang on the PAM-distal side of the cleavage site (16,20). In contrast, Cas12a processes its own ~40 nt guide RNAs (crRNA) from primary transcripts, requires a T-rich PAM that is distal to the cleavage site, uses a single RuvC domain to sequentially cleave each strand of the DNA target, typically leaves 5' overhangs on the cleavage products, and remains bound to the PAM-proximal cleaved DNA while the PAM-distal piece of DNA dissociates (11,(21)(22)(23)(24)(25)(26). Recent work has identified an additional activity attributed to Cas12a, specifically that Cas12a ribonucleoprotein (RNP) remains in an activated state by remaining bound to the crRNA and PAM proximal DNA after release of the cleaved, PAM distal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule techniques are powerful tools for dissecting dynamic protein-nucleic acid interactions and have been employed to study types I, II, and V CRISPR-Cas systems (Blosser et al, 2015;Chen et al, 2017;Dagdas et al, 2017;Dillard et al, 2018;Jeon et al, 2018;Lim et al, 2016;Loeff et al, 2018;Osuka et al, 2018;Redding et al, 2015;Rutkauskas et al, 2015;Singh et al, 2016Singh et al, , 2018Sternberg et al, 2014;Szczelkun et al, 2014;Xue et al, 2017;Yang et al, 2018). Here, we used single-molecule fluorescence microscopy to investigate the targeting mechanism of a type III-A Cas10-Csm complex.…”
Section: Introductionmentioning
confidence: 99%